REDUCTION OF MORTADELLA COOKING TIME AND EVALUATION OF THE FINAL PRODUCT QUALITY - Orsolin, Diones (2015)
In food industry, the cooking is one of the most important processes for the conservation and qualityassurance of the final product, especially mortadella. However, this process requires high investmentin modern equipment besides having energy and steam expenses.. In this context, the objective of thisstudy was to propose a cooking method of mortadella produced with pork and chicken, by reducingtime and increasing temperature inside the baking oven. Evaluations of behavior of water activity,pH and texture of the mortadella were carried out throughout shelf life. From the results, we foundthat both pork and chicken mortadella that were cooked by the current process and those that passedthrough the cooking process with reduced time showed no significant differences at the level of 95%confidence for the analyzed characteristics. Therefore, all treatments had similar values and can beconsidered within the established standards of product quality for both water activity and for pH andtexture.Keywords: chicken meat; pork meat; texture; water activity.